Risk management and insurance - Trieschmann, James S.; Gustavson, Sandra G.; Hoyt, Robert E. (Cincinnati, Ohio : South-Western College, 2001)
This book is divided into five parts: Risk and the risk management process; Commercial risk management applications; Personal risk management applications; Risk management applications; and The risk management environment.
Keywords: United States; Insurance; Risk management; Insurance -- United States; Risk management -- United States